Freaks of History Two Performance Texts - MacDonald, James (Intellect, 2017)
Disability studies have long been the domain of medical and pedagogical academics. However, in recent years, the subject has outgrown its clinical origins. In Freaks of History, James MacDonald presents two dramatic explorations of disability within the wider themes of sexuality, gender, foreignness, and the Other. Originally directed by Martin Harvey and performed by undergraduate students at the University of Exeter, Wellclose Square and Unsex Me Here analyze cultural marginalization against the backdrop of infamous historical events.